Positive Feedback Regulation of Type I IFN Production by the IFN-Inducible DNA Sensor cGAS - Ma, Feng; Li, Bing; Liu, Su-yang; Iyer, Shankar S; Yu, Yongxin; Wu, Aiping; Cheng, Genhong (The Journal of immunology (1950), 2015)
Rapid and robust induction of type I IFN (IFN-I) is a critical event in host antiviral innate immune response. It has been well demonstrated that cyclic GMP-AMP (cGAMP) synthase (cGAS) plays an important role in sensing cytosolic DNA and triggering STING dependent signaling to induce IFN-I. However, it is largely unknown how cGAS itself is regulated during pathogen infection and IFN-I production. In this study, we show that pattern recognition receptor (PRR) ligands, including lipid A, LPS, poly(I:C), poly(dA:dT), and cGAMP, induce cGAS expression in an IFN-I–dependent manner in both mouse and human macrophages. Further experiments indicated that cGAS is an IFN-stimulated gene (ISG), and two adjacent IFN-sensitive response elements (ISREs) in the promoter region of cGAS mediate the induction of cGAS by IFN-I. Additionally, we show that optimal production of IFN-β triggered by poly (dA:dT) or HSV-1 requires IFNAR signaling. Knockdown of the constitutively expressed DNA sensor DDX41 attenuates poly(dA:dT)-triggered IFN-β production and cGAS induction. By analyzing the dynamic expression of poly(dA:dT)-induced IFN-β and cGAS transcripts, we have found that induction of IFN-β is earlier than cGAS. Furthermore, we have provided evidence that induction of cGAS by IFN-I meditates the subsequent positive feedback regulation of DNA-triggered IFN-I production. Thus, our study not only provides a novel mechanism of modulating cGAS expression, but also adds another layer of regulation in DNA-triggered IFN-I production by induction of cGAS.